2018
DOI: 10.1021/acs.macromol.7b02533
|View full text |Cite
|
Sign up to set email alerts
|

Color-Coding Visible Light Polymerizations To Elucidate the Activation of Trithiocarbonates Using Eosin Y

Abstract: We report mechanistic investigations into aqueous visible-light reversible addition−fragmentation chain transfer (RAFT) polymerizations of acrylamides using eosin Y as a photoinduced electron-transfer (PET) catalyst. The photoinduced polymerization was found to be dependent upon the irradiation wavelength and reagents, where either reduction or oxidation of the PET catalyst leads to inherently different initiation and reversible-termination steps. Using blue light, multiple mechanisms of initiation are observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
171
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(179 citation statements)
references
References 51 publications
8
171
0
Order By: Relevance
“…To our amazement, only the nondeoxygenated reaction achieved polymerization with an excellent agreement between the theoretical and experimental (GPC) molecular weights (M n ), and an arrow molecular weight distribution (MWD, M w /M n = 1.09). [17] To test this hypothesis,w ea dded triethylamine (TEA) at 1equivalence to the trithiocarbonate for the polymerization of MA under both aerobic and anaerobic conditions (Supporting Information, Table S1, entries 5,6). [6] Kinetic investigation of N,N-dimethylacrylamide (DMA) under aerobic conditions revealed that the polymerization progressed in al inear fashion after as hort (ca.…”
mentioning
confidence: 99%
“…To our amazement, only the nondeoxygenated reaction achieved polymerization with an excellent agreement between the theoretical and experimental (GPC) molecular weights (M n ), and an arrow molecular weight distribution (MWD, M w /M n = 1.09). [17] To test this hypothesis,w ea dded triethylamine (TEA) at 1equivalence to the trithiocarbonate for the polymerization of MA under both aerobic and anaerobic conditions (Supporting Information, Table S1, entries 5,6). [6] Kinetic investigation of N,N-dimethylacrylamide (DMA) under aerobic conditions revealed that the polymerization progressed in al inear fashion after as hort (ca.…”
mentioning
confidence: 99%
“…This means that there is a high likelihood of being able to expand the method to proteins which are more sensitive to the presence of small organic molecules. A mechanistic study on this type Eosin Y catalyzed PET‐RAFT has been very recently performed by Sumerlin and coworkers …”
Section: Applications Of Aqueous Photochemical Raft and Atrpmentioning
confidence: 99%
“…b) Esterase activity against p‐ NP of conjugate and lipase adsorbed on a glass slide after drying and washing. Reproduced with permission . Copyright 2018, Elsevier.…”
Section: Applications Of Aqueous Photochemical Raft and Atrpmentioning
confidence: 99%
“…Photo‐RAFT with photoinitiator, RAFT without exogenous catalyst/initiator (iniferter), and photoinduced electron/energy transfer RAFT (PET‐RAFT) have roused growing concern for the well‐controlled features and the accelerated polymerization rates . More recently, a library of photocatalysts including phthalocyanine compounds, Eosin Y, zinc tetraphenylporphyrin (ZnTPP) and crude extracted chlorophyll were disclosed, which could mediate the polymerizations under visible and near‐infrared light even in the presence of oxygen . The combination of microflow technique and photoinduced RAFT and iniferter polymerization will be discussed below.…”
Section: Continuous Flow Photoinduced Degenerative Transfer Rdrpmentioning
confidence: 99%